2021
DOI: 10.1039/d1ra06534c
|View full text |Cite
|
Sign up to set email alerts
|

Searching and designing potential inhibitors for SARS-CoV-2 Mpro from natural sources using atomistic and deep-learning calculations

Abstract: The hybrid DeepFrag/atomistic simulation approach could lead to a new scheme for developing SARS-CoV-2 3CLpro/Mpro inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…DeepFrag calculations were designed to predict the structural change of the inhibitor that may enhance the ligand-binding affinity [ 34 , 35 ]. In particular, the ML model was successfully applied to the SARS-CoV-2 Mpro + inhibitor [ 38 ]. The ligand-binding affinity was then confirmed via FPL simulations [ 38 ], which revealed a correlation coefficient with the respective experiment of [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DeepFrag calculations were designed to predict the structural change of the inhibitor that may enhance the ligand-binding affinity [ 34 , 35 ]. In particular, the ML model was successfully applied to the SARS-CoV-2 Mpro + inhibitor [ 38 ]. The ligand-binding affinity was then confirmed via FPL simulations [ 38 ], which revealed a correlation coefficient with the respective experiment of [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the ML model was successfully applied to the SARS-CoV-2 Mpro + inhibitor [ 38 ]. The ligand-binding affinity was then confirmed via FPL simulations [ 38 ], which revealed a correlation coefficient with the respective experiment of [ 32 ]. The hybrid approaches were thus utilized to modify the structure of nirmatrelvir, which may lead to a novel compound forming stronger binding affinity to the protease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptonigrin tetracyclic aminoquinoline-5,8 dione is an antitumor antibiotic and a previous screening against SARS-CoV-2 nsp15 endoribonuclease identi ed as positive hit [23]. Scillaren A, is a cardiac glycoside derived from Drimia species [24] and in silico studies reported to have SARS CoV-2 Mpro binding a nities [25]. Proscillaridin, is a cardiac glycoside isolated from Drimia maritima, an anticancer drug that inhibits DNA topoisomerase I and II [26].…”
Section: Discussionmentioning
confidence: 99%
“…Streptonigrin tetracyclic aminoquinoline-5,8 dione is an antitumor antibiotic, and previous screening against SARS-CoV-2 nsp15 endoribonuclease identified it as a positive hit [ 24 ]. Scillaren A is a cardiac glycoside derived from Drimia species [ 25 ] and in silico studies have been reported to have SARS-CoV-2 Mpro binding affinities [ 26 ]. In our present study, Scillaren A inhibits pseudovirion infection and Spike S1 binding.…”
Section: Discussionmentioning
confidence: 99%